The taxonomic revision of Asian Aristolochia (Aristolochiaceae) I: Confirmation and illustration of A. austroszechuanica, A. faucimaculata and A. yunnanensis var. meionantha from China - Zhu, Xin-Xin; Liao, Shuai; Zhang, Lin; Wang, Zhang-Hua; Du, Cheng; Ma, Jin-Shuang (Phytotaxa, 2016)
Through extensive field work, careful examination of numerous specimens, and color photos taken in the field and study in relation to published accounts of Aristolochia (Aristolochiaceae), we conclude that A. austroszechuanica, A. faucimaculata and A. yunnanensis var. meionantha are distinct species. Detailed morphological comparisons with related species, descriptions and illustrations are presented. A. yunnanensis var. meionantha is raised into Aristolochia meionantha. Furthermore, detailed distributions, citation of studied specimens and nomenclatural notes for these species are also provided.